Coiled-Coil and C2 Domain-Containing Protein 1A (CC2D1A) Promotes Chemotherapy Resistance in Ovarian Cancer - Kumar, Sanjeev; Oien, Derek B.; Khurana, Ashwani; Cliby, William; Hartmann, Lynn; Chien, Jeremy; Shridhar, Viji (Frontiers in Oncology, 2019)
Recurrence within six months of the last round of chemotherapy is clinically defined as platinum-resistant ovarian cancer. Gene expression associated with early recurrence may provide insights into platinum resistant recurrence. Prior studies identified a 14-gene model that accurately predicted early or late recurrence in 86% of patients. One of the genes identified was CC2D1A (encoding coiled-coil and C2 domain containing 1A), which showed higher expression in tumors from patients with early recurrence. Here, we show that CC2D1A protein expression was higher in cisplatin-resistant ovarian cancer cell lines compared to cisplatin-sensitive cell lines. In addition, immunohistochemical analysis of patient tumors on a tissue microarray (n = 146) showed that high levels of CC2D1A were associated with a significantly worse overall and progression-free survival (p = 0.0002 and p = 0.006, respectively). To understand the contribution of CC2D1A in chemoresistance, we generated shRNA-mediated knockdown of CC2D1A in SKOV3ip and PEO4 cell lines. Cell death and clonogenic assays of these isogenic clonal lines clearly showed that downregulation of CC2D1A resulted in increased sensitivity to cisplatin and paclitaxel in ovarian cancer cells. Moreover, nude mice bearing SKOV3ip xenografts with stably downregulated CC2D1A were more sensitive to chemotherapy as evidenced by a significantly longer survival time compared to xenografts derived from cells stably transduced with non-targeting shRNA. These results suggest CC2D1A promotes chemotherapy resistance in ovarian cancer.